2022
DOI: 10.1038/s41567-022-01641-9
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulation of phenotypic noise synchronizes emergent organization and active transport in confluent microbial environments

Abstract: The variation associated with different observable characteristics—phenotypes—at the cellular scale underpins homeostasis and the fitness of living systems. However, if and how these noisy phenotypic traits shape properties at the population level remains poorly understood. Here we report that phenotypic noise self-regulates with growth and coordinates collective structural organization, the kinetics of topological defects and the emergence of active transport around confluent colonies. We do this by catalogui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Although many earlier studies have already investigated how nonmotile bacteria construct three-dimensional structures, most of them have focused on the process where isolated cells grow and form circular colonies ( 21 , 23 , 24 , 26 , 30 ). In this situation, it has been reported that the in-plane stress derived from cell growth is maximized at the center of the colony ( 26 , 35–37 ), which causes a few cells to be verticalized first, locally, near the center ( 21 , 23 , 26 ).…”
Section: Relation To Circular Colonies Formed From Isolated Cellsmentioning
confidence: 99%
“…Although many earlier studies have already investigated how nonmotile bacteria construct three-dimensional structures, most of them have focused on the process where isolated cells grow and form circular colonies ( 21 , 23 , 24 , 26 , 30 ). In this situation, it has been reported that the in-plane stress derived from cell growth is maximized at the center of the colony ( 26 , 35–37 ), which causes a few cells to be verticalized first, locally, near the center ( 21 , 23 , 26 ).…”
Section: Relation To Circular Colonies Formed From Isolated Cellsmentioning
confidence: 99%
“…Topological defects, which are singularities in local orientational field, are associated with a breakdown of local orientational order and thus, regions of low values of S are markers of the presence of defects [14]. In case of bacterial colonies, only +1 / 2 and −1 / 2 defects were observed, as is well known [11, 15]. In our case, we observed that topological defects of both +1 / 2 and −1 / 2 charge proliferate in the vicinity of the enclave interface (Fig.…”
Section: Genealogical Interface As a Hotspot Of Orientational Disordermentioning
confidence: 99%
“…Cells in confluent bacterial colonies show several remarkable features of self organisation [10, 11, 12, 13] and the importance of structural order and topological attributes of cell organisation in optimising growth of such colonies has been highlighted [14, 15]. In particular, singularities in local ordering of cells in colonies, referred to as topological defects, have been implicated in driving the formation of layers in biofilms for both motile and sessile bacteria [16, 17], which marks a significant step in biofilm growth and maturation.…”
Section: Introductionmentioning
confidence: 99%
“…In active bio-colloidal microbial systems [17][18][19], typically, speciesspecific methods are required to grow the relevant species and prepare appropriate buffers for running the experiments. Additional parameters, including interfacial entrapment, physiological growth stages, external cues, and intrinsic stress levels, are experimentally relevant since these factors directly control the activity of the microbial systems [20][21][22][23][24][25], and, thus modulate the emergent drying patterns. Furthermore, underlying substrates play a crucial role in droplet fate, depending on their surface energy (wetting vs. non-wetting) and topography.…”
mentioning
confidence: 99%